Time preferences and their life outcome correlates: Evidence from a representative survey - Dániel Horn; Hubert János Kiss (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2019)
We collect data on time preferences of a representative sample of the Hungarian population in a non-incentivized way and investigate how patience and present bias associate with important life outcomes in five domains: i) educational attainment, ii) unemployment, iii) income and wealth, iv) financial decisions and difficulties, and v) health. Based on the literature, we formulate the broad hypotheses that patience fosters, while present bias hinders positive outcomes in the domains under study. We document a consistent and often significant positive effect of patience in almost all areas (except unemployment), with the strongest effects in escaping low educational attainment, wealth and financial decisions. We find that present bias associates significantly with saving decisions and financial troubles.
Keywords: D12; D14; D31; D90; I12; I21; J6; 330; educational attainment; financial decisions and difficulties; income and wealth; patience; present bias; risk preferences